Understanding the deterrent impact of U.S. overseas forces - Frederick, Bryan; Watts, Stephen; Lane, Matthew; Doll, Abby; Rhoades, Ashley L.; Smith, Meagan L. (RAND, 2020)
In the aftermath of Russian military aggression against Ukraine in 2014, and with increasing tensions in the U.S.- China strategic competition, the question of whether U.S. overseas military presence can enhance deterrence remains central. At the same time, U.S. overseas military commitments are increasingly coming under question at home, both among the public at large and among many foreign- and defense-policy elites. This report provides empirical evidence on the deterrent effects of U.S. overseas military forces. It investigates how these effects might vary by the type, size, and location of these forces. The analyses provide the clearest evidence in support of the deterrent effect of heavy ground forces, particularly when deployed near but not directly bordering potential adversaries. The analyses show that the more mobile forces are, the less evidence there is of a deterrent effect. The report also assesses the effects of the deployment of U.S. forces during crises, finding that, although they can help avoid escalation and maintain the status quo, they are not necessarily well suited to altering the long-term strategic dynamics between states.
"Arroyo Center" -- Titelseite
Keywords: USA -- Army; Einsatz; Stationierung; Ausland; Deterrence (Strategy); United States / Armed Forces / Foreign countries; Military bases, American / Foreign countries; Security, International; Armed Forces; United States